A Cognitive Processes of PGSD Students in Solving Algebra Literacy Problems: Proses Kognitif Mahasiswa PGSD dalam Memecahkan Masalah Literasi Aljabar - Rizal Masaniku; Hikmahturrahman Hikmahturrahman (Journal of Innovative and Creativity, 2025)
This study aims to explore the cognitive processes of PGSD students in solving algebraic literacy problems. This study is qualitative in nature, using a case study approach. The subjects in this study were two PGSD students with high mathematical ability. The instruments used were one algebraic literacy question and interview guidelines. The methods used for data collection were tests, interviews, and documentation. The data analysis techniques used included data condensation, data presentation, and conclusion drawing. The results of this study indicate that PGSD students in the high category have mature algebraic literacy. SKT1 demonstrates analytical, reflective, and systematic cognitive processes in interpreting information and explicitly constructing mathematical models. Meanwhile, SKT2 displays efficient, strategic, and abstractive thinking with logical model simplification. Both are able to relate calculation results to the problem context in a meaningful way, reflecting the integration of conceptual, procedural, and reflective understanding in algebraic thinking.